2010
DOI: 10.1175/2010mwr3334.1
|View full text |Cite
|
Sign up to set email alerts
|

Convective Snowbands Downstream of the Rocky Mountains in an Environment with Conditional, Dry Symmetric, and Inertial Instabilities

Abstract: Convective snowbands moved slowly over Wyoming and northern Colorado on 16-17 February 2007 and produced up to 71 mm (2.8 in.) of snow that was unpredicted by operational numerical weather prediction models and human forecasters. The northwest-southeast-oriented bands lasted for over 6 h, comprising both a single major band (more than 30 km wide) and multiple minor bands (about 10 km wide). The convective bands initiated within the ascending branch of a secondary circulation associated with both near-surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
65
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 49 publications
5
65
0
Order By: Relevance
“…Convective snowbands under similar synoptic conditions were also documented by Snook (1992) and Davis (1997) in Colorado and by Milrad et al (2014) in Alberta, Canada. Schumacher et al (2010) also found that the bands formed on the low-momentum side of potential vorticity (PV) banners downstream of the Rocky Mountains, which suggested a means to anticipate their formation in the future.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Convective snowbands under similar synoptic conditions were also documented by Snook (1992) and Davis (1997) in Colorado and by Milrad et al (2014) in Alberta, Canada. Schumacher et al (2010) also found that the bands formed on the low-momentum side of potential vorticity (PV) banners downstream of the Rocky Mountains, which suggested a means to anticipate their formation in the future.…”
Section: Introductionmentioning
confidence: 93%
“…In contrast, the cause of the minor bands was less clear. Schumacher et al (2010) ruled out gravity waves, horizontal convective rolls, the release of moist symmetric instability, and orographic bands in saturated flow. Instead, Schumacher et al (2010) hypothesized that the release of low-to midtropospheric dry symmetric instability (as well as conditional and inertial instabilities) on the anticyclonic-shear side of a midlevel jet streak may have been responsible.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations